Analysis of the Relationship Between Social Media Use with the Students Entrepreneurial Interest and Entrepreneurial Behavior of Culinary Arts Education at Universitas Negeri Semarang - Valeria Zebua; Muhammad Ansori; Siti Fatonah; Octavianti Paramita (Universitas Negeri Semarang, 2024)
In addition to being a source of information and a means of communication, social media emerges with its various advanced features that support business development and make it easier for individuals to find out the turnover of business creations from interactions and communication with others on social media networks. This will encourage the creation of entrepreneurial opportunities both new and developing existing opportunities to meet consumer demand in the market. In this study, research was conducted on students as internet users in the majority group according to their age.According to the theory of uses and effects, social media will have an effect on its users, with this it is expected that students will grow their interest in entrepreneurship and entrepreneurial behavior in line with the high level of entrepreneurship. According to the theory of uses and effects, social media will have an effect on its users, with this it is expected that students will grow their entrepreneurial interest and entrepreneurial behavior in line with the high use of social media. This study aims to relationship of social media use with entrepreneurial interest and entrepreneurial behavior of culinary education students at Semarang State University. The sample taken was 145 respondents determined using probability sampling technique. Data were collected using a questionnaire instrument. Data analysis using normality test, simple correlation test and multiple correlation test.The results showed a significant and positive relationship between the use of social media with interest in entrepreneurship with a calculated r value of 0.429 which means it has a moderate level of relationship. The relationship between the use of social media with entrepreneurial behavior also shows a significant and positive relationship with a calculated r value of 0.428 with a level of relationship closeness included in the medium level. Similarly, the relationship of entrepreneurial interest with entrepreneurial behavior has a calculated r value of 0.603 which means it has a high level of relationship and shows a significant and positive relationship. Simultaneously significant relationship between the use of social media with entrepreneurial interest and entrepreneurial behavior with a value of R / correlation coefficient of 0.479 and the level of relationship at a moderate level.